Atypical homodimerization revealed by the structure of the (S)-enantioselective haloalkane dehalogenase DmmarA from Mycobacterium marinum - Snajdarova, Karolina; Marques, Sérgio M; Damborsky, Jiri; Bednar, David; Marek, Martin (Acta crystallographica. Section D, Structural biology, 2023)
Haloalkane dehalogenases (HLDs) are a family of α/β-hydrolase fold enzymes that employ SN2 nucleophilic substitution to cleave the carbon-halogen bond in diverse chemical structures, the biological role of which is still poorly understood. Atomic-level knowledge of both the inner organization and supramolecular complexation of HLDs is thus crucial to understand their catalytic and noncatalytic functions. Here, crystallographic structures of the (S)-enantioselective haloalkane dehalogenase DmmarA from the waterborne pathogenic microbe Mycobacterium marinum were determined at 1.6 and 1.85 Å resolution. The structures show a canonical αβα-sandwich HLD fold with several unusual structural features. Mechanistically, the atypical composition of the proton-relay catalytic triad (aspartate-histidine-aspartate) and uncommon active-site pocket reveal the molecular specificities of a catalytic apparatus that exhibits a rare (S)-enantiopreference. Additionally, the structures reveal a previously unobserved mode of symmetric homodimerization, which is predominantly mediated through unusual L5-to-L5 loop interactions. This homodimeric association in solution is confirmed experimentally by data obtained from small-angle X-ray scattering. Utilizing the newly determined structures of DmmarA, molecular modelling techniques were employed to elucidate the underlying mechanism behind its uncommon enantioselectivity. The (S)-preference can be attributed to the presence of a distinct binding pocket and variance in the activation barrier for nucleophilic substitution.
Keywords: Aspartic Acid; enantioselectivity; SAXS; substrátová specifita; stereoizomerie; kyselina asparagová; DmmarA; Hydrolases; Mycobacterium marinum; X-ray crystallography; haloalkane dehalogenases; homodimerization; surface loops; Substrate Specificity; hydrolasy; Stereoisomerism